2018
DOI: 10.1128/jvi.01589-17
|View full text |Cite
|
Sign up to set email alerts
|

Size, Composition, and Evolution of HIV DNA Populations during Early Antiretroviral Therapy and Intensification with Maraviroc

Abstract: Residual viremia is common during antiretroviral therapy (ART) and could be caused by ongoing low-level virus replication or by release of viral particles from infected cells. ART intensification should impact ongoing viral propagation but not virion release. Eighteen acutely infected men were enrolled in a randomized controlled trial and monitored for a median of 107 weeks. Participants started ART with ( = 9) or without ( = 9) intensification with maraviroc (MVC) within 90 days of infection. Levels of HIV DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 70 publications
(98 reference statements)
2
14
0
Order By: Relevance
“…Second, eliminating the reservoir is not a problem of blocking viral replication, but is rather a problem of eliminating all the infected cells that carry infectious proviruses, at least some of which have clonally expanded. It is likely that the forces which drove the clonal expansion in the first place will still be present following the administration of a curative therapy, such as "kick and kill" (44). Even if a strategy is found that activates the expression of all of the infectious proviruses in the cells of a particular clone, leading to the elimination of that clone, it is not clear that such a strategy would be able to successfully activate all of the infectious proviruses that are in all of the different clones of expanded cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, eliminating the reservoir is not a problem of blocking viral replication, but is rather a problem of eliminating all the infected cells that carry infectious proviruses, at least some of which have clonally expanded. It is likely that the forces which drove the clonal expansion in the first place will still be present following the administration of a curative therapy, such as "kick and kill" (44). Even if a strategy is found that activates the expression of all of the infectious proviruses in the cells of a particular clone, leading to the elimination of that clone, it is not clear that such a strategy would be able to successfully activate all of the infectious proviruses that are in all of the different clones of expanded cells.…”
Section: Discussionmentioning
confidence: 99%
“…Every cell that carries a fully intact provirus has the potential to release infectious virus that could rekindle the infection. Although it has been possible to eliminate large masses of tumor tissue with immunotherapy, the tumor cells that respond to immunotherapy express antigens that make it possible to target them (44). If, as appears to be the case, most of the HIV-infected cells that carry intact proviruses do not express viral RNA or proteins, eliminating the HIV-infected cells that carry fully intact proviruses will require a strategy that activates the expression of the proviruses in all, or almost all, of the cells that carry latent infectious proviruses or an alternative strategy that prevents any expressed virus from rekindling a systemic infection.…”
Section: Discussionmentioning
confidence: 99%
“…We employed one genetic distance-based test (56) and one tree-based test (57), both of which were implemented in the HyPhy (v2.22) program (58). For the distance-based test, we employed the Hudson, Boos, and Kaplan nonparametric test for population structure (56), a test that has been validated for within-host HIV data sets (59), including from the reservoir, where it is sometimes referred to as the "nonparametric test for panmixia" (59)(60)(61). This test compares the mean pairwise distances between sequences from different subpopulations versus the same subpopulation (compartmentalization is supported if the mean pairwise distances of sequences from the same subpopulation are smaller than those from different subpopulations) and computes the K ST statistic, whose values range from 0 (denoting no compartmentalization) to 1 (denoting complete compartmentalization).…”
Section: Methodsmentioning
confidence: 99%
“…The possibility of ongoing HIV replication in sanctuaries, where drug penetration is suboptimal, and its potential contribution to the residual viremia roused a considerable interest in drug intensification: adding one or more antiretroviral drugs to boost the ART regimen [91][92][93][94][95][96][97][98][99][100]. Most intensification studies added an INSTI (raltegravir or dolutegravir) to the ART regimen.…”
Section: Impact Of Art Intensification On Residual Viremia and Other mentioning
confidence: 99%
“…Therefore, its effect on 2-LTR circles and RV was explained by possible HIV latency reversal and induction of residual replication by the drug [112][113][114]. However, other groups failed to show any effect of maraviroc on 2-LTR circles or RV [98,115]. Interestingly, the addition of maraviroc to a raltegravir-based ART regimen in individuals starting ART resulted in a faster decline of plasma viremia, as well as lower levels of total HIV DNA and 2-LTR circles in the intensified arm [116], suggesting that suppression of HIV replication by INSTI-based regimens may also be incomplete.…”
Section: Impact Of Art Intensification On Residual Viremia and Other mentioning
confidence: 99%